Effects of Palatable Food Versus Thin Figure Conflicts on Responses of Young Dieting Women - Chen, Shuaiyu; Jackson, Todd; Dong, Debo; Zhuang, Qian; Chen, Hong (Frontiers in Psychology, 2019)
Many young women use dieting to achieve a thinner figure yet most tend to fail as a result of heightened responsiveness to palatable food environments and increases in hedonic cravings. In this preliminary study, we developed a novel palatable food vs. thin figure conflict task to assess conflicting motives associated with eating among young women. Forty young dieting women (mean body mass index (BMI) = 22.98 kg/m2, SD = 3.81) completed a food vs. figure conflict task within a 2 (distractor image: food vs. figure) × 2 (word-image congruence: congruent vs. incongruent) within-subjects design. Results supported the view that this new task could effectively capture conflict costs. Dieting young women displayed stronger food conflicts than figure conflicts based on having longer response delays and higher error rates in the food conflict condition than the figure conflict condition. Although young women often proclaimed “dieting” to achieve or maintain a good figure, dieters appeared to exhibit stronger preferences for palatable food cues relative to thin figure cues. These results provide important information for understanding automatic processing biases toward palatable foods and underscore the need for research extensions in other cultural contexts to determine whether such biases are universal in nature.